Design of Dual Priority Persistent CSMA Protocol Based on FPGA. Issue 6 (April 2019) - Lu, Xu; Ding, Hongwei; Yang, Jundong; Xu, Zhi; Bao, Liyong; He, Min
Abstract: In order to study the MAC layer protocol in the wireless sensor network under the actual channel condition, the field programmable gate array (FPGA) hardware circuit is used to provide a dual-priority implementation scheme for the persistence carrier sense multiple access (CSMA) protocol. According to the characteristics of each node in the network, analyzes the system throughput and energy consumption, and the FPGA is used to overcome the shortcomings of the existing implementation scheme and the article combines the actual application, changes the single channel mode, and realizes the dual channel data transmission. Finally, the simulation tests the correctness of the design.